2019
DOI: 10.1155/2019/3879626
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Induced by Delay in a Nutrient‐Phytoplankton Model with Multiple Delays

Abstract: A nutrient-phytoplankton model with multiple delays is studied analytically and numerically. The aim of this paper is to study how the delay factors influence dynamics of interaction between nutrient and phytoplankton. The analytical analysis indicates that the positive equilibrium is always globally asymptotically stable when the delay does not exist. On the contrary, the positive equilibrium loses its stability via Hopf instability induced by delay and then the corresponding periodic solutions emerge. Especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…However, in the real aquatic environments, the growth of phytoplankton is generally in uenced by many biotic and abiotic factors, such as light [5], cell size [6], climate [7], grazer [8], carbon dioxide [9], nutrient [10], and temperature [11], which make it difficult to determine a clear mechanism of phytoplankton blooms only through experimental studies. Actually, many ecologists, biologists, and biomathematicians increasingly realize that a mathematical model is a powerful tool for exploring biological and physical processes on the dynamic mechanisms of phytoplankton growth in relation to different factors qualitatively and quantitatively [12,13], as the research results can help us to find out the key factors that may induce the blooms of phytoplankton but are difficult to predict in the experimental analysis, to answer that what the growth mechanism of phytoplankton is, to predict possibly when the phytoplankton blooms will occur, and to determine the optimal strategy for possible control of phytoplankton blooms [14][15][16][17][18][19][20][21][22][23][24][25]. e application of mathematical models in other research fields, such as investigating other predator-prey dynamics or infectious disease dynamics, can be found in [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the real aquatic environments, the growth of phytoplankton is generally in uenced by many biotic and abiotic factors, such as light [5], cell size [6], climate [7], grazer [8], carbon dioxide [9], nutrient [10], and temperature [11], which make it difficult to determine a clear mechanism of phytoplankton blooms only through experimental studies. Actually, many ecologists, biologists, and biomathematicians increasingly realize that a mathematical model is a powerful tool for exploring biological and physical processes on the dynamic mechanisms of phytoplankton growth in relation to different factors qualitatively and quantitatively [12,13], as the research results can help us to find out the key factors that may induce the blooms of phytoplankton but are difficult to predict in the experimental analysis, to answer that what the growth mechanism of phytoplankton is, to predict possibly when the phytoplankton blooms will occur, and to determine the optimal strategy for possible control of phytoplankton blooms [14][15][16][17][18][19][20][21][22][23][24][25]. e application of mathematical models in other research fields, such as investigating other predator-prey dynamics or infectious disease dynamics, can be found in [26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In 1949, Riley et al [38] first used the mathematical model to study the nutrient-plankton dynamics, which leads to the formulation of a growing number of mathematical models to describe the nutrient-phytoplankton dynamics or nutrient-plankton dynamics, and many dynamic mechanisms of phytoplankton growth response to various factors have been revealed [14,15,22,[39][40][41][42][43][44][45][46][47]. For example, Chen et al [43] showed that the proper control of the ratio for nitrogen and phosphorus can more effectively control and eliminateblue-green algae blooms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since time delay indeed exists in various growth process of phytoplankton, for example, nutrient convert by phytoplankton, and mathematical models can provide quantitative insights into the dynamics of phytoplankton growth systems. Therefore, mathematical models interactions with time delay are more preferred used in study of phytoplankton growth . In addition, Dai et al indicated that patchy spatial patterns can emerge because of a time delay in the growth response of phytoplankton.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mathematical models interactions with time delay are more preferred used in study of phytoplankton growth. [40][41][42][43][44] In addition, Dai et al 45 indicated that patchy spatial patterns can emerge because of a time delay in the growth response of phytoplankton.…”
Section: Introductionmentioning
confidence: 99%